Pengaruh Variasi Bahan: Pelarut dan Lama Ekstraksi Ultrasonik dari Ekstrak Daun Kelor terhadap Rendemen dan Kadar Total Fenol - Rifkia, Via; Revina, Rika (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: Moringa (Moringa oleifera L.) is a plant that has a wide range of health benefits. The benefits of Moringa can be obtained from the leaf part. One of the compounds that are in Moringa leaves and have benefits is phenol compounds. Phenol compounds were tested from Moringa leaf extract obtained using the ultrasonic method. The ultrasonic method is an extraction method that can produce extracts effectively and efficiently. The purpose of this study was to determine the effect of variations in material concentration: solvent (1:10, 1:15, and 1:20) and extraction duration (10, 20, and 30 minutes) on the yield value and total phenol content of Moringa leaf extract. The extract obtained is then weighed and calculated the yield value. After that, Moringa leaf extract was tested for phytochemical screening and total phenol level test. Based on the results of the study, it showed that the highest amendment value of Moringa leaf extract was obtained from the ratio of ingredients: solvent 1:20 b / v with an extraction time of 30 minutes, which was 35.89%. Then the highest total phenol content results were obtained from moringa leaf ethanol extract at the ratio of ingredients: solvent 1:20 b / v with an extraction time of 30 minutes, which was 25,9 GAE/g.